Digital marketing strategies on retail sector in Cali (2019)
Currently, the society is immersed in knowledge. The global economy has transformed, the main assets now are neither physical nor financial, but are intellectuals. Knowledge and ideas are driving the extent of growth in economy, rather than by traditional resources of the earth, such as, raw materials, labor and capital. As a result, there is a need to take better advantage of knowledge, understanding it as a key factor for social development that allows to strengthen the competitiveness of organizations. Although, it is essential to highlight that in the present, the approach towards online shopping trends is taking great impact in organizations, where it is necessary to direct the processes of both products and services. Thus, leading to entities regulators select to create standards for those organizations that are in the process of launching a product or service to the market, comply with the quality standards for online sale and thus not avert the consumer. The most popular marketing variables are product, price, place and promotion, known as 4 Ps. Depending on the purpose of each company, a combination of variables may be resulting in the ideal marketing mix in order to reach consumers and position a product. However, an appropriate strategy to attract a segment of customers and achieve retain a profit long term may be the most important (Kotler, 2007). Moreover, traditional marketing channels have been replaced or complemented by the Internet. Online platforms are developed where businesses can move into more competitive markets, record more information and measure faster the effectiveness of strategy. New media are emerged supported by Information technologies a using the 4 Ps world in order to reach final consumers (Cruz Herradon, 2009).